Long-Term Followup of Adolescent and Young Adult Females with Hypergonadotropic Hypogonadism - Tsimaris Pantelis; Vrachnis Nikolaos; Iliodromiti Zoe; Deligeoroglou Efthymios (International Journal of Endocrinology)
The condition characterized by elevated gonadotrophins (gonadotropins elevated into the menopausal range), low sex steroids, and menstrual disorders was previously termed Premature Ovarian Failure (POF). However, over the last two years an effort has been made by many authors to have the term Primary Ovarian Insufficiency (POI) exclusively applied. Irrespective of the term, the condition concerns adolescent and young adult women under 40 years who experience cessation of menstruation for more than 3 cycles (whereas these women in the past had a rhythmic menstrual cycle) or amenorrhea for 4–6 months against the background of a previously disturbed menstrual cycle. Determining the cause of POI is difficult, and it is even harder to deal with problems arising from the paucity of estrogen as well as to draw up the plan for long-term monitoring of these patients. This paper presents long-term therapeutic management strategies concerning emotional health, hormone replacement therapy, maintenance of bone health, family planning, other associated disorders as well as possible research options for the future.